Cumulative Effects of Environmental Change on Culturally Significant Ecosystems in the Inuvialuit Settlement Region + Supplementary Appendices 1 to 3 (See Article Tools) - Tyson, William; Lantz, Trevor C.; Ban, Natalie C. (ARCTIC, 2016)
The Inuvialuit Settlement Region (ISR) in the western Canadian Arctic is experiencing environmental changes that affect subsistence harvesting practices and are of concern to local communities. In order to assess the impacts of multiple disturbances on culturally important ecosystems in the ISR, we created a cumulative disturbance map that represents relative intensity of terrestrial disturbances across the study region. We then assessed the relative level of environmental disturbance in important harvesting areas and management zones. Subsequently, we modeled nine future disturbance scenarios that included combinations of increased human impacts and more frequent and widespread wildfires. Using the conservation planning software Marxan, we assessed the potential to conserve large, contiguous areas of unaffected harvesting lands across all scenarios. Our results show that important management zones, wildlife harvesting areas, and community planning zones are all affected by environmental disturbances. Marxan optimizations show that existing disturbance levels create thresholds for current conservation potential and indicate that future disturbances will further limit conservation potential. These results suggest that conservation planners in the region must take steps to anticipate more widespread natural and human-caused disturbance in the ISR and work to maintain large contiguous landscapes that can support wildlife harvesting in the face of ongoing environmental disturbance. La région désignée des Inuvialuit (RDI) dans l’ouest de l’Arctique canadien connaît des changements environnementaux qui ont des incidences sur les méthodes de récolte. Ces incidences sont également à la source d’inquiétudes chez les collectivités de la région. Afin d’évaluer les incidences de perturbations multiples sur les écosystèmes de la RDI revêtant une importance culturelle, nous avons créé une carte des perturbations cumulatives représentant l’intensité relative des perturbations terrestres dans toute la région visée par ...